Philosophy of administration: classical approaches of administration in the light of philosophical thought (Research, Society and Development, 2020)
This theoretical paper describes the philosophy as a science that can help the administrator in his career. Presents the influence of Western philosophical exerted on the administration and common themes are discussed in light of philosophical thought. Seeks to demonstrate the importance of philosophical reflection on management functions with emphasis on the philosophy of Socrates; the Cartesian method developed by French philosopher Rene Descartes was used in an analogy with the quality tool developed by Ishikawa (Ishikawa Diagram), and then the same thought is put under the lens of complexity theory of Edgar Morin; the philosophy of Nietzsche was related to the characteristics of entrepreneurs, where the philosopher's thoughts relate to the profile approached by the authors on entrepreneurship; the Aristotelian thought was used to demonstrate how philosophy can enhance productivity. Is pointed out the particular subject matter, and the importance of the philosophy as a reflexive and alternative literature to managers and scholars.